AI Mood Tracking Application - Ng Wai Kit,; ENCIK MOHD ZAKI BIN MOHD SALIKON, (Applied Information Technology And Computer Science, 2024)
Journaling is an activity that allows users to record events, feelings, and thoughts throughout the day. This aids meditation and self-discovery by allowing users to solidify their thoughts in the journaling media. However, journaling is not widespread as it is seen as unengaging, inconvenient to think and write, and ineffective at improving their day-to-day. The project aims to create a mobile AI Mood Tracking Application that uses sentiment analysis AI to determine the user’s mood based on their journal entry. The application also provides reflection prompts and guided solutions to handle the mood detected. It also allows students to communicate with their corresponding counselors to create user interaction engagement. The application interface uses Flutter, while the back end uses Firebase. The AI model is trained using the GoEmotions dataset. The Agile Development Model divides the development into the planning, design, development, testing, deployment, review, and launch phases. The project is a step towards creating a practical journaling application for the mental-health-conscious modern generation. Future research can be done to perform testing and refinement of the application to increase the impact and acceptance among users. Further fine-tuning the AI Mood Tracking Application can adapt to be an effective tool that induces profound personal development in the user via deep and effective journaling, analysis, and reflection.